2017
DOI: 10.1007/s00426-017-0893-3
|View full text |Cite
|
Sign up to set email alerts
|

Communication for coordination: gesture kinematics and conventionality affect synchronization success in piano duos

Abstract: Ensemble musicians often exchange visual cues in the form of body gestures (e.g., rhythmic head nods) to help coordinate piece entrances. These cues must communicate beats clearly, especially if the piece requires interperformer synchronization of the first chord. This study aimed to (1) replicate prior findings suggesting that points of peak acceleration in head gestures communicate beat position and (2) identify the kinematic features of head gestures that encourage successful synchronization. It was expecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 34 publications
1
41
0
5
Order By: Relevance
“…Studying the synchronization of note onsets between the performers would be a natural extension of the study, to link the factors contributing to musical synchronization with the cues used to coordinate interaction [ 23 ]. For instance, Bishop & Goebl [ 96 ] have found that note-level synchrony is related to kinematic features of communicative head gestures. Such a shift to a lower temporal level (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Studying the synchronization of note onsets between the performers would be a natural extension of the study, to link the factors contributing to musical synchronization with the cues used to coordinate interaction [ 23 ]. For instance, Bishop & Goebl [ 96 ] have found that note-level synchrony is related to kinematic features of communicative head gestures. Such a shift to a lower temporal level (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Communication between performers is thought to support action prediction processes by providing cues to initiate the simulation process. While auditory communication in the form of a musical sound signal is usually sufficient for performers to maintain temporal coordination, they sometimes supplement their audio signals with visual signals (Badino et al, 2014 ; Kawase, 2014 ; Bishop and Goebl, 2017 ). Ensemble musicians are better able to predict the course of observed gestures when those gestures fall within their practiced repertoire (Wöllner and Cañal-Bruland, 2010 ; Bishop and Goebl, 2014 ), and better able to predict such gestures than are novice musicians (Luck and Nte, 2008 ; Petrini et al, 2009 ; Lee and Noppeney, 2014 ).…”
Section: Mechanisms For Musical Creativitymentioning
confidence: 99%
“…Breathing gestures are likely used as well and have the benefit of providing an audiovisual cue, but they are more difficult to measure experimentally. Cueing gestures can be exchanged at moments of sudden tempo or meter change (Kawase, 2014 ) or at piece entrances or re-entrances that require synchronization between performers (Bishop and Goebl, 2015 , 2017 ). These are ambiguous, isolated moments when co-performer's expectations about how to play might not otherwise align.…”
Section: Mechanisms For Musical Creativitymentioning
confidence: 99%
“…During ensemble performance, visual communication between musicians is secondary in importance to auditory communication, but can become more relevant when performers are uncertain of each other’s interpretations ( Bishop & Goebl, 2015 ). Prior research has shown that temporal instability, such as happens at piece entrances, long pauses, and sudden tempo changes ( Bishop and Goebl, 2017 , Davidson, 2012 , Kawase, 2014a , Kawase, 2014b ), and disruptions to the clarity (e.g., loudness) of inter-performer audio feedback ( Fulford, Hopkins, Seiffert, & Ginsborg, 2018 ) can prompt an exchange of visual cues. These are sometimes deliberately integrated into a performance plan across rehearsals ( Williamon & Davidson, 2002 ).…”
Section: Introductionmentioning
confidence: 99%